Analisis Bauran Pemasaran Kuritos di Desa Linau Kecamatan Maje Kabupaten Kaur - Ratna Sudjanawati; Reflis; Yuliarti, Ellys; Khairani, Lathifah (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
The study was carried out in Linau Village, Maje District, Kaur Regency, with the objective of analyzing the marketing mix, specifically examining the impact of product, price, promotion, and distribution channels on Kuritos. A descriptive qualitative approach was utilized. Primary data were gathered firsthand through interviews and direct observations involving the owners, employees of the Kuritos Cracker Industry, and its consumers. Secondary data were obtained from relevant literature on marketing mix research. Data collection techniques included observation, interviews, and documentation, while data analysis encompassed data reduction, presentation, and drawing conclusions.The findings reveal that product-related strategies focus on improving quality and introducing innovations, such as designing more appealing packaging. Pricing strategies involve offering discounts and conducting market condition analyses. Promotional activities are carried out through word-of-mouth and digital platforms, such as WhatsApp, Facebook, and Instagram. Distribution strategies emphasize using more strategic locations, like food centers and tourist attractions, and collaborating with distributors. The study underscores the critical role of these elements in optimizing Kuritos' marketing strategy, demonstrating how their effective application enhances market presence and overall success.